Association of BMI and Hormonal Imbalance with Primary and Secondary Infertility: A Cross-Sectional Study - Huria Dardar; Sara Abdulla; Amina Abdulrazeg; Agzail Elhddad (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. This cross-sectional study aims to evaluate the relationship of body mass index (BMI) and hormonal imbalance with primary and secondary infertility among 160 infertile Libyan women. Methods. We had collected the basic demographic data and laboratory hormone profile of infertile patients attended Fertility Center Albayda complaining of primary or secondary infertility. Results. The outcomes yielded a significant difference among the ages when related to the infertility type. Moreover, in the primary infertility group, a significant negative correlation of luteinizing hormone(LH) and follicle-stimulating hormone (FSH) with BMI was observed. In secondary infertility, serum FSH levels demonstrated a significant negative correlation with BMI. Upon division of the sample into obese and non-obese groups, significantly higher LH levels in the non-obese group were observed. Conclusion. We concluded that obesity can results in hormonal derangements, which may adversely influence fertility. Cite this article. Dardar H, Abdulla S, Abdulrazeg A, Elhddad A. Association of BMI and Hormonal Imbalance with Primary and Secondary Infertility: A Cross-Sectional Study. Alq J Med App Sci. 2022;5(2):565-572. https://doi.org/10.5281/zenodo.7401777